Isotropic damage phenomena in saturated porous media: a bem formulation - Lima Junior, Eduardo Toledo de (2011)
This work is devoted to the numerical analysis of saturated porous media, taking into account the damage phenomenon on the solid skeleton. The porous media is taken into poroelastic framework, in full-saturated condition, based on the Biot\'s Theory. A scalar damage model is assumed for this analysis. An implicit Boundary Element Method (BEM) formulation, based on time-independent fundamental solutions, is developed and implemented to couple the fluid flow and the elasto-damage problems. The integration over boundary elements is evaluated by using a numerical Gauss procedure. A semi-analytical scheme for the case of triangular domain cells is followed to carry out the relevant domain integrals. The non-linear system is solved by a Newton-Raphson procedure. Numerical examples are presented, in order to validate the implemented formulation and to illustrate its efficiency.